PROBLEMATIKA PENGGUNAAN DESAIN INDUSTRI PADA ALAT MUSIK TRADISIONAL - Kurniawan, Budi (Paraguna, 2017)
Industrial  Design  Act No.  31  of 2000 provides protectiontoany   ornamental  or aesthetic  aspect  of  an   article.  Hence,  it  gives  widestopportunity  to  people  to createa  creativedesign.  On  the  other  side,  Traditional  MusicInstrument  which is  partoffolkloreortraditional  cultural  expression(TCE)  insome  way  still  give an   opportunity  to  anyone  also   to  add   an   element  and   or  make    new   design inherenttoinstruments.A mix  betweenpublicowned rightsof TraditionalMusic Instrument  and  theprivaterightofIndustrial  Designarisenew  problemin  legal sense  including  to  define  an   exact  definition  ofa  "novelty"  element  adhere  in every   Industrial  Design  application  submitted.  Thefactthat  Industrial  Design Office  is   in   a   passive  standing  when  they  accept  a  new   Industrial  Design's application  bothfrom  a  good  faith's  creator   oreven    abadfaith'screatormake theoffice  couldnotrejectthat  applicationuntil  some   onepropose  an  objection. On  the    other  side,    legal   awareness  of  interested  parties,   in   this  case,   are traditional   music   instruments    manufacturers    who   have   been     producing instruments  for  manyyearsare   stilllow  when  opposeon  suchproblems.  This article  will  focus  on  reviewing  "a  novelty"  element  adhere  in   every   on   a  new application  ofIndustrial  Designsubmittedfaced  on"anotnovelty"  elementwhich isarisinginTraditionalMusic  Instruments  base.